Consistently inconsistent: Multimodal episodic deficits in semantic aphasia. (16th March 2020) - Cogdell-Brooke, Lucy; Stampacchia, Sara; Jefferies, Elizabeth; Violante, Inês R.; Thompson, Hannah E.
Abstract: Semantic Aphasia (SA) patients have difficulty accessing semantic knowledge in both verbal and non-verbal tasks appropriately for the current context. Automatically activated semantic knowledge overwhelms the system, because it is no longer able to inhibit interference from dominant meanings in order to select weaker alternatives. Episodic memory, like semantic memory, requires control to select relevant memories amongst competing episodes. For example, our memory for what we ate for breakfast last Saturday is affected by competition from numerous other breakfast meals eaten on other days. Where one is unable to guide retrieval, we may rely on automatically activated knowledge about "breakfast foods", and therefore experience false memories. Brain systems that support semantic control are also implicated in episodic control, and therefore deficits in semantic control are likely to cause more widespread problems. Despite this, nearly all research to date focuses on semantic performance alone. This study explored the impact of this semantic impairment on episodic recall. We used a verbal and non-verbal episodic memory task: participants remembered nursery rhymes in the verbal condition and logos and their associated products in the visual condition (e.g. bowl of cereal and coco-pops ). For both tasks, we manipulated a) congruency with pre-existing knowledge (e.g. expectancy of trials: baa baa black build – instead of sheep ) and b) whether these trial types were blocked by congruency or mixed, as well as (c) distractor strength. If SA patients experience overwhelming automatic activation, they should find incongruent items more difficult to suppress, particularly when presented in an unpredictable task format. A total of 13 SA patients were compared to 33 controls across three experiments. In line with our predictions, SA patients found it more difficult to retrieve episodic memories which were in conflict with pre-existing semantic knowledge. This was true across modalities. Moreover, these deficits were accentuated when the congruency was presented in a mixed fashion, and so unpredictable across trials. Evidence of these episodic control impairments in SA cases supports the idea of a shared mechanism for semantic and episodic memory control. Highlights: Deficits of control in semantic aphasia affect episodic retrieval. Semantic aphasia patients demonstrate an over-reliance on automatic activation. Patients will select semantically related information over correct newly encoded information. They display inconsistent performance across experiments which probe similar processes. A shared mechanism may exist between semantic and episodic retrieval.